Comparative genome-wide analysis of WRKY transcription factors in two Asian legume crops: Adzuki bean and Mung bean. Issue 1 (December 2018) - Srivastava, Richa; Kumar, Sanjeev; Kobayashi, Yasufumi; Kusunoki, Kazutaka; Tripathi, Prateek; Kobayashi, Yuriko; Koyama, Hiroyuki; Sahoo, Lingaraj
Abstract The seminal participation of WRKY transcription factors in plant development, metabolism and in the governance of defense mechanism implicated their gaining importance for genomic and functional studies. The recent release of draft genome sequences of two legume crops, Adzuki bean (Vigna angularis ) and Mung bean (Vigna radiata ) has paved the way for characterization of WRKY gene family in these crops. We found 84WRKY genes in Adzuki bean (VaWRKY ) and 85WRKY genes in Mung bean (VrWRKY ). Based on the phylogenetic analysis, VaWRKY genes were classified into three groups with 15 members in Group I, 56 members in Group II, and 13 members in Group III, which was comparable toVrWRKY distribution in Mung bean, 16, 56 and 13 members in Group I, II and III, respectively. The few tandem and segmental duplication events suggested that recent duplication plays no prominent role in the expansionVaWRKY andVrWRKY genes. The illustration of gene-structure and their encoded protein-domains further revealed the nature of WRKY proteins. Moreover, the identification of abiotic or biotic stress-responsivecis -regulatory elements in the promoter regions of someWRKY genes provides fundamental insights for their further implementation in stress-tolerance and genetic improvement of agronomic traits.